1986
DOI: 10.3382/ps.0650749
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin D3 on Leg Abnormalities in Broilers

Abstract: Variable quantities of vitamin D3 (D3) ranging from 0 to 20,000 IU D3/kg of diet were incorporated in a corn-soybean meal basal diet and fed to male broiler chicks from day-old until 56 days of age. Four experiments were conducted to determine: 1) the requirement of D3 for growth and bone calcification of normal chicks, 2) the requirement of D3 for deficient chicks, and 3) if feeding up to 20,000 IU D3/kg of diet affects bone metabolism or increases the incidence of leg abnormalities. The parameters measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 4 publications
1
7
2
1
Order By: Relevance
“…Considering the main effects of vitamin D, and the interactions of vitamin A x vitamin D and vitamin D x vitamin K with body weight gain and feed efficiency, it was apparent that increasing vitamin D level in the diet of starting chicks to at least 1,000 ICU/kg with appropriate levels of other fat soluble vitamins improved weight gain and feed efficiency. Lofton and Soares (1986) did not show the same response to increasing D levels in broilers. The negative effect of simultaneous presence of excessive levels of vitamin A and vitamin D on weight gain in this study does not agree with the observation reported by Payne and Manston (1967) in cattle, where the two vitamins at high levels seemed to depress toxic effects of each other.…”
Section: Discussioncontrasting
confidence: 50%
“…Considering the main effects of vitamin D, and the interactions of vitamin A x vitamin D and vitamin D x vitamin K with body weight gain and feed efficiency, it was apparent that increasing vitamin D level in the diet of starting chicks to at least 1,000 ICU/kg with appropriate levels of other fat soluble vitamins improved weight gain and feed efficiency. Lofton and Soares (1986) did not show the same response to increasing D levels in broilers. The negative effect of simultaneous presence of excessive levels of vitamin A and vitamin D on weight gain in this study does not agree with the observation reported by Payne and Manston (1967) in cattle, where the two vitamins at high levels seemed to depress toxic effects of each other.…”
Section: Discussioncontrasting
confidence: 50%
“…The results of this work indicated that the level of vitamin D3 in the broilers diet was effective in improving body weights of the chicks. Based on the data, the predicted requirement of concentration of cholecalciferol for BW gain (1500 to 3500 IU/kg of diet during the starter and finisher phases) was considerably higher than the concentration (200 IU/kg) recommended by the NRC (1994) or those of several authors (400 to 1000 IU/kg) (Lofton and Soares, 1986; Goff and Horst, 1995; Kasim and Edwards, 2000; Fritts and Waldroup, 2003). The lower concentrations recommended by these authors might be due to the adequate concentrations of Ca and P (approximately 1.0 and 0.7% respectively) used in the basal diets.…”
Section: Discussionmentioning
confidence: 80%
“…The supplementation of CD leaf powder to the normal diet at 0.25% level showed improvement in the body weight of the birds as well as the feed conversion ratio. Lofton and Soares [26] indicated that less than 5.0 g vitamin D 3 /kg diet produced significantly lower body weight, reduced feed consumption and feed conversion values, serum calcium, and tibia breaking strength and percentage tibial ash. That 0.25% CD powder fed chicks showed better performance in terms of feed conversion ratio, bone strength and calcification, compared to other groups, suggests that the quantity of 1,25(OH) 2 D 3 present in diet at 0.25% [2.5 g 1,25(OH) 2 D 3 /kg diet] of C. diurnum could be the optimum level to derive the maximum benefits in the birds.…”
Section: Discussionmentioning
confidence: 98%